2017
DOI: 10.1016/j.humov.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Task-related and person-related variables influence the effect of low back pain on anticipatory postural adjustments

Abstract: Background People with low back pain exhibit altered postural coordination that has been suggested as a target for treatment, but heterogeneous presentation has rendered it difficult to identify appropriate candidates and protocols for such treatments. This study evaluated the associations of task-related and person-related factors with the effect of low back pain on anticipatory postural adjustments. Methods Thirteen subjects with and 13 without low back pain performed seated, rapid arm flexion in self-init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…Because this study investigated healthy participants, additional work utilizing multiple APA paradigms is needed to establish the extent of APA-task invariance in populations with clinical disorders that associate with modified anticipatory postural behavior [5,[28][29][30]. Indeed, the extent of task-invariance itself may be an indicator of disrupted control.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study investigated healthy participants, additional work utilizing multiple APA paradigms is needed to establish the extent of APA-task invariance in populations with clinical disorders that associate with modified anticipatory postural behavior [5,[28][29][30]. Indeed, the extent of task-invariance itself may be an indicator of disrupted control.…”
Section: Discussionmentioning
confidence: 99%
“…Following our results, SIJD individuals showed lower values of APAs at the affected side before any interventions. As there were no similar studies in the literature, we could only compare the current results with those studies reported for CLBP (12,16,20,(33)(34)(35). Some of these studies reported increased postural sway while a few ones showed smaller postural sway for the CLBP group.…”
Section: Before Interventionmentioning
confidence: 74%
“…In other words, anticipatory reactions are launched by the individual, and then the CNS makes anticipatory corrections to predict postural perturbations. A group of studies suggested a complex relationship between LBP and APAs and decreased variability of APA onset latencies (16)(17)(18). Reaction time (RT) is the time interval from applying a stimulus to response, which could be increased in musculoskeletal disorders like LBP (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired postural control has been reported to involve APAs and CPAs of trunk muscles [ 28 , 29 ]. Most previous studies reported that delayed activation of abdominal muscles, especially TrA, in patients with CNLBP was commonly observed in patients with LBP in the postural control assessment, which may increase the recurrence of LBP in patients with CNLBP [ 4 , 30 , 31 ]. The potential reason was that the delayed muscle activation time of TrA in the APAs of patients with CNLBP was associated with remodeling of the motor cortex [ 32 ].…”
Section: Discussionmentioning
confidence: 99%